Foreign-Law Bonds: Can They Reduce Sovereign Borrowing Costs? - Marcos Chamon; Julian Schumacher; Christoph Trebesch (Journal of International Economics, 2018)
Governments often issue bonds in foreign jurisdictions, which can provide additional legal protection vis-á-vis domestic bonds. This paper studies the effect of this jurisdiction choice on bond prices. We test whether foreign-law bonds trade at a premium compared to domestic-law bonds. We use the euro area 2006-2013 as a unique testing ground, controlling for currency risk, liquidity risk, and term structure. Foreign-law bonds indeed carry significantly lower yields in distress periods, and this effect rises as the risk of a sovereign default increases. These results indicate that, in times of crisis, governments can borrow at lower rates under foreign law.
Keywords: F34; G12; K22; 330; sovereign debt; creditor rights; seniority; law and finance